2006
DOI: 10.1002/pmic.200500046
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis cell wall proteome defined using multidimensional protein identification technology

Abstract: With the completion of the sequencing of the Arabidopsis genome and the recent advances in proteomic technology, the identification of proteins from highly complex mixtures is now possible. Rather than using gel electrophoresis and peptide mass fingerprinting, we have used multidimensional protein identification technology (MudPIT) to analyse the "tightly-bound" proteome for purified cell walls from Arabidopsis cell suspension cultures. Using bioinformatics for the prediction of signal peptides for targeting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
0
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(242 citation statements)
references
References 37 publications
11
220
0
11
Order By: Relevance
“…These proteins, misassigned in Elortza et al (2003) as 1,3-bglucanases, were also assessed for their expression levels as EST abundance and as MPSS (massive parallel signature sequencing; http://mpss.udel.edu/grape/) outputs. Interestingly, the MPSS data record high expression levels for PDCB1 in Arabidopsis callus; Arabidopsis suspension culture was the source material for our original proteomic analysis (Bayer et al, 2006). The predicted and biochemically verified GPI nature of these proteins was supported by our indirect observations that their subcellular location was stabilized by an inhibitor of phospholipase C, an activity for which GPI-anchor proteins are very vulnerable (Svetek et al, 1999).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…These proteins, misassigned in Elortza et al (2003) as 1,3-bglucanases, were also assessed for their expression levels as EST abundance and as MPSS (massive parallel signature sequencing; http://mpss.udel.edu/grape/) outputs. Interestingly, the MPSS data record high expression levels for PDCB1 in Arabidopsis callus; Arabidopsis suspension culture was the source material for our original proteomic analysis (Bayer et al, 2006). The predicted and biochemically verified GPI nature of these proteins was supported by our indirect observations that their subcellular location was stabilized by an inhibitor of phospholipase C, an activity for which GPI-anchor proteins are very vulnerable (Svetek et al, 1999).…”
Section: Discussionmentioning
confidence: 51%
“…Previous work (Bayer et al, 2006) identified a series of membraneassociated proteins from cell wall preparations of Arabidopsis suspension cells. As part of a survey of the subcellular targeting of these proteins as fusions to fluorescent markers, we have identified At5g61130 as a gene encoding a novel Pd protein.…”
Section: At5g61130 Encodes a Plasmodesmal Proteinmentioning
confidence: 99%
“…Defining proteins that change in abundance, form, location or other activities may indicate the presence and functional significance of a protein. Whereas comparative ECM proteome research is quite advanced in animals (Zhu et al, 2007) and yeast (Kim et al, 2007) (Liepman et al, 2010;Basu et al, 2006;Bayer et al, 2006;Borderies et al, 2003;Chivasa et al, 2002;Feiz et al, 2006;Jamet et al 2008a), Medicago sativa (Soares et al, 2007;Watson et al, 2004), and crop plants for, e.g., Oryza sativa (Choudhary et al, 2010), Brassica napus (Basu et al, 2006) Zea mays (Zhu et al, 2006) and Cicer arietinum (Bhushan et al, 2006). Around 500 CWPs of Arabidopsis, representing about one third of its estimated cell wall proteome, have been described (Liepman et al, 2010) while 219, 143, 102, 58 CWPs were identified in rice, chickpea, maize and Brassica, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, this methods still suffers some of the disadvantages seen in 2D gel electrophoresis, in particular limited sensitivity and resolution to detect low molecular weight proteins (Chakravarti et al, 2004). In contrast, multidimensional protein identification technology (MudPIT) is more widely used as a sensitive method (Bayer et al, 2006;Chen et al, 2006;Guzzetta and Chien et al, 2005;Durr et al, 2004). In MudPIT a complex protein mixture is digested with a specific protease (most commonly trypsin).…”
Section: Fishing For "Gold Standard" Cancer Biomarkers: Great Expectamentioning
confidence: 99%